Prevalence of bronchiectasis in inflammatory bowel disease: a systematic review and meta-analysis - Ma, Yu; Qiang, Zhihui; Zhou, Miaomiao; Zhang, Tianyi; Li, Zhuoyang; Zhong, Haicheng; Chang, Yue; Ning, Zimeng; Liu, Yun (Frontiers in Medicine, 2024)
Objective: The aim of this study was to conduct a systematic review and meta-analysis of the incidence of inflammatory bowel disease-associated bronchiectasis (IBD-BE) and to explore the possible risk factors for IBD-BE, which could help to understand the pulmonary involvement in patients with IBD and to determine the global incidence of the disease. Methods: We searched PubMed and EMBASE databases to identify information on the prevalence of IBD-BE among IBD patients in the published literature. Information was extracted on study design, country, year, IBD-BE testing method, IBD characteristics, number of IBD-BE cases and total number of IBD patients, and factors associated with IBD-BE. We conducted meta-analyses using random-effects or fixed-effects models to estimate the prevalence of IBD-BE among IBD patients.Results: Out of a total of 682 studies, we identified 16 studies that reported prevalence. These studies used a heterogeneous approach to identify IBD-BE. In these 16 studies, there were 92,191 patients with IBD, of whom 372 cases of IBD-BE were identified. The prevalence of IBD-BE in studies using HRCT imaging was 12% (95% CI 4-39%) using a randomeffects model. When only retrospective studies with sample sizes greater than 100 (n=6) were considered, the prevalence was 1% (95% CI 0-1%). However, when only retrospective studies with sample sizes less than 100 were included (n=4), the prevalence was 29% (95% CI 6-100%); in prospective studies (n=6), the combined prevalence was 11% (95% CI 4-29%). we performed a subgroup analysis of the differences in the incidence of IBD-BE between the different studies, each of which we subgrouped by type of study, type of disease, duration of disease, and diagnostic modality, and the results showed no significance. Conclusion: In this systematic review and meta-analysis, the prevalence of IBD-BE was 12% among studies with HRCT imaging, suggesting that bronchiectasis may be an underestimated common extraintestinal manifestation of IBD. Asymptomatic patients with IBD-BE may present with abnormalities on HRCT or pulmonary function tests. Future studies should standardize methods to identify IBD-BE cases and investigate the natural history and clinical course given the relatively high prevalence among IBD.